2010
DOI: 10.1124/mol.110.068577
|View full text |Cite
|
Sign up to set email alerts
|

Activated Sterol Regulatory Element-Binding Protein-2 Suppresses Hepatocyte Nuclear Factor-4-Mediated Cyp3a11 Expression in Mouse Liver

Abstract: Sterol regulatory element-binding protein-2 (SREBP-2) is a key transcription factor for the cholesterol homeostasis. Recent studies have suggested the association of CYP3A enzymes, major drug-metabolizing enzymes, with cholesterol metabolism. In the present study, we have investigated a possible involvement of SREBP-2 in hepatic Cyp3a11 expression. Feeding a low-cholesterol diet (LCD) to mice activated hepatic SREBP-2 whereas it attenuated hepatic Cyp3a11 expression. These phenomena were reversed by cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In summary, the results of the present study showed that expression of genes encoding enzymes involved in cholesterol biosynthesis is enhanced via the activation of SREBP-2 in the livers of Cyp3a Ϫ / Ϫ mice, possibly due to the decreased formation of oxysterols. Because dietary cholesterol has been reported to affect gene expression of CYP3A enzymes (49)(50)(51), the present observations suggest that CYP3A enzymes play a role in maintaining cholesterol levels at a constant level in the liver. The results of the present study also showed that total cholesterol levels were also decreased by 20% in the livers of Cyp3a Ϫ / Ϫ mice, possibly due to enhanced bile acid synthesis by elevation of CYP7A1 in Cyp3a Ϫ / Ϫ mice.…”
Section: Effects Of Cyp3a Defi Ciency On Expression Levels Of Cholestmentioning
confidence: 73%
See 1 more Smart Citation
“…In summary, the results of the present study showed that expression of genes encoding enzymes involved in cholesterol biosynthesis is enhanced via the activation of SREBP-2 in the livers of Cyp3a Ϫ / Ϫ mice, possibly due to the decreased formation of oxysterols. Because dietary cholesterol has been reported to affect gene expression of CYP3A enzymes (49)(50)(51), the present observations suggest that CYP3A enzymes play a role in maintaining cholesterol levels at a constant level in the liver. The results of the present study also showed that total cholesterol levels were also decreased by 20% in the livers of Cyp3a Ϫ / Ϫ mice, possibly due to enhanced bile acid synthesis by elevation of CYP7A1 in Cyp3a Ϫ / Ϫ mice.…”
Section: Effects Of Cyp3a Defi Ciency On Expression Levels Of Cholestmentioning
confidence: 73%
“…Interestingly, it has been reported that feeding a low-cholesterol diet to mice attenuates hepatic Cyp3a11 expression by activating hepatic SREBP-2 ( 49 ). Activated SREBP-2 has been suggested to interact with peroxisome proliferator-activated receptor ␥ coactivator 1 ␣ (PGC1 ␣ ) in the mouse liver, resulting in reduced PGC1 ␣ recruitment to hepatocyte nuclear factor-4 ␣ on the Cyp3a11 promoter and subsequent downregulation of Cyp3a11 expression ( 49 ). Conversely, feeding high-cholesterol diets to rats has been reported to increase expression and activity of CYP3A ( 50 ).…”
Section: Effects Of Cyp3a Defi Ciency On Expression Levels Of Cholestmentioning
confidence: 99%
“…Chromatin immunoprecipitation coupled with massively parallel sequencing was used to detect several FXR-binding sites in mouse FXR target genes such as Shp and Ost˛/ˇ [27]. This report suggested that Shp consists of two FXR-responsive elements located in the promoter region and downstream enhancer.…”
Section: Discussionmentioning
confidence: 98%
“…Sixty-seven hours after transfection, the cells were treated with 0.1 M GW4064 for 5 h. Chromatin immunoprecipitation (ChIP) assays were performed as described previously [27,28] with minor modifications. After crosslinking with 1% formaldehyde and sonication of the cells, supernatant was obtained by centrifugation, and a portion of the supernatant was retained as the input sample.…”
Section: Chromatin Immunoprecipitation Assaymentioning
confidence: 99%
“…While CYP3A11 is mainly known as a major drug-metabolizing P450 enzyme, there is evidence that it also plays a role in cholesterol and bile acid metabolism (33,34). It has also been shown that highcholesterol feeding as well as LXRα or LXRα/β deficiency lead to dramatic upregulation of Cyp3a11 expression in mouse liver and overall Cyp3a11 mRNA levels correlate with the liver cholesterol content, suggesting that Cyp3a11 may mediate a compensatory response to cholesterol overload (35,54). These data strongly suggest that upregulation of Cyp27a1 and Cyp3a11 expression in L-ΔID animals is likely responsible for the observed changes in the bile acid pool composition and improved cholesterol tolerance.…”
Section: Discussionmentioning
confidence: 99%